2020
DOI: 10.1002/jnr.24646
|View full text |Cite
|
Sign up to set email alerts
|

Localizing the seizure onset zone by comparing patient postictal hypoperfusion to healthy controls

Abstract: Arterial spin labeling (ASL) MRI can provide seizure onset zone (SOZ) localizing information in up to 80% of patients. Clinical implementation of this technique is limited by the need to obtain two scans per patient: a postictal scan that is subtracted from an interictal scan. We aimed to determine whether it is possible to limit the number of ASL scans to one per patient by comparing patient postictal ASL scans to baseline scans of 100 healthy controls. Eighteen patients aged 20–55 years underwent ASL MRI <… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…Consistent with findings found in animal studies, human neuroimaging studies have clearly delineated postictal hypoperfusion in the vicinity of the seizure onset zone and up to 90 minutes after seizure termination by means of two different imaging methodologies: arterial spin labeling (ASL)–perfusion MRI and computed tomography-perfusion (CTP) (Gaxiola-Valdez et al, 2017; Li et al, 2019; Perera et al, 2020). Moreover, Liu and colleagues studied patients with forebrain focal epilepsies using ASL MRI and found postictal hypoperfusion of medullary brainstem respiratory centres following generalized seizures providing evidence for the increased risk of SUDEP seen in bilateral tonic clonic seizures over other seizure types (Liu et al, 2020).…”
Section: Discussionsupporting
confidence: 69%
“…Consistent with findings found in animal studies, human neuroimaging studies have clearly delineated postictal hypoperfusion in the vicinity of the seizure onset zone and up to 90 minutes after seizure termination by means of two different imaging methodologies: arterial spin labeling (ASL)–perfusion MRI and computed tomography-perfusion (CTP) (Gaxiola-Valdez et al, 2017; Li et al, 2019; Perera et al, 2020). Moreover, Liu and colleagues studied patients with forebrain focal epilepsies using ASL MRI and found postictal hypoperfusion of medullary brainstem respiratory centres following generalized seizures providing evidence for the increased risk of SUDEP seen in bilateral tonic clonic seizures over other seizure types (Liu et al, 2020).…”
Section: Discussionsupporting
confidence: 69%
“…Nevertheless, at present, the actual application of ASL for the presurgical evaluation of epilepsy is still rare. Several studies have reported the localization value of ASL, such as in MRI-negative children with new onset seizures, mesial temporal lobe epilepsy, nonlesional focal impaired awareness seizures, intractable epilepsy, partial epilepsy status, and localizing the seizure onset zone [ 6 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, at present the actual application of ASL in the presurgical evaluation of epilepsy is still rare. Several studies have reported that the localization value of ASL, such as in MRI negative children with new onset seizures, mesial temporal lobe epilepsy, non-lesional focal impaired awareness seizures, intractable epilepsy, partial epilepsy status, and localizing the seizure onset zone [13][14][15][16][17][18][19] . Epilepsy can induce cortical hyperperfusion during seizures, especially following repeated seizures or status epilepticus.…”
Section: Discussionmentioning
confidence: 99%